Form of presentation of traditional Ma'barutung music in Parombean village, Curio district, Enrekang regency - Ekomagrah Warsono; Widodo Widodo; Wadiyo Wadiyo (The International Journal of Politics and Sociology Research, 2023)
Ma'Barutung is one of the traditional cultures inherited from their ancestors which is still maintained by the Massenrempulu community, especially in Parombean Village, Curio District, Enrekang Regency. Ma'barutung is a traditional music that uses bamboo as its main musical instrument and the type of bamboo used is pattung tara bamboo with a size of 1 meter. Ma'barutung music is a routine activity for local residents and has become a tradition in Parombean Village which is performed on certain occasions so that this music becomes an important tradition in which there are unique offerings in each performance. Ma'barutung music is also very guarded by the people of Parombean village because this art is the only art inherited from their ancestors that has cultural values ​​and character education values ​​in its performances. This research approach uses an ethnomusicological approach. data collection technique; observation techniques, interview techniques and documentation. This study aims to analyze and discuss the form of presentation of ma'barutung music.